1998
DOI: 10.1161/01.cir.97.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive In Vivo Clot Dissolution Without a Thrombolytic Drug

Abstract: In vivo arterial clot dissolution can be achieved with intravenous microbubbles and transcutaneous ultrasound delivery alone. This technique has potential for clinical application in patients with acute arterial and venous thrombotic occlusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(27 citation statements)
references
References 6 publications
0
26
0
1
Order By: Relevance
“…In vitro and in vivo studies have confirmed this on several scales ranging from tiny to large clots [27, 30, 31,38,39,40,41,42,43]. In vitro examples show a predominately mechanical effect of the bubble encountering the clot and eroding it when activated by ultrasound [27, 30, 38].…”
Section: Clot Lysis With Ultrasound and Microbubbles Without Thrombolmentioning
confidence: 92%
See 1 more Smart Citation
“…In vitro and in vivo studies have confirmed this on several scales ranging from tiny to large clots [27, 30, 31,38,39,40,41,42,43]. In vitro examples show a predominately mechanical effect of the bubble encountering the clot and eroding it when activated by ultrasound [27, 30, 38].…”
Section: Clot Lysis With Ultrasound and Microbubbles Without Thrombolmentioning
confidence: 92%
“…Moreover, optimal microbubble dosage, delivery, required thrombolytic drug dosage, and optimal ultrasound characteristics all remain uncertain [28,29,30,31,32]. Microbubbles that have been used for thrombolysis include lipid, albumin, or galactose spheres ranging in size from 0.5 to about 5 µm surrounding a gas or air bubble.…”
Section: Microbubble-enhanced Thrombolysis With Tissue Plasminogen Acmentioning
confidence: 99%
“…Thrombolytic efficacy is dependent on intensity and on duration of exposure [5]. Combination with an ultrasound contrast agent may further enhance the therapeutic effect [6,7,8,9]. There are reports on clinical studies that have shown an improvement of recanalisation rates and clinical outcome of stroke patients treated with rt-PA when diagnostic ultrasound was applied simultaneously [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is used in catheter-based ultrasound thrombolysis [16]. Effective clot dissolution also occurs when ultrasound is applied over a distance, with a more pronounced effect in the presence of an echo contrast agent [4,5,6, 17]. This opens up the possibility of external, i.e., non-invasive application of therapeutic ultrasound without a thrombolytic drug in acute vessel occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…6 Multiple animal studies, including intracranial clot lysis in pigs, have confirmed this concept. [7][8][9][10][11] Cavitation has been theorized to cause mechanical stress on the surface of the thrombus leading to its destabilization. 12 Microbubble administration dramatically lowers the threshold for cavitation and increases the lytic activity of ultrasound.…”
mentioning
confidence: 99%